Hubungan Fungsi Supervisi dengan Kepatuhan Perawat Menjalankan SOP Identifikasi Pasien Di RSUP Dr Mohammad Hoesin Palembang Tahun 2015 - Fitrirachmawati, Fitrirachmawati (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Supervision is a form supervisory that aim to improve the staf performance through a systematic process in the provision of motivation, communication and guidance. This study used an observational design with cross sectional approach using stratified random sampling. The purpose of this study was to determine the relationship between the function of head room supervision with the compliance of nurses in performing SOP patient identification. The result of this research using Chi Square test to prove there is a significant correlation between motivation, communication and guidance to compliance of nurses in implementating SOP of patient identification (p value < α). The conclusion of this study is that the functions of the supervision of head room had a substantial role to improve the nurse complaince in conducting the patient identification based on the SOP.